Functional requirements for guided bone regeneration/guided tissue regeneration membrane design: Progress and challenges - Zhan, Huilu; Shi, Ruijianghan; Ni, Haohao; Li, Haiyan; Yuan, Changyong; Lin, Kaili; Sculean, Anton; Miron, Richard J. (Periodontology 2000, 2025)
Guided tissue regeneration (GTR) and guided bone regeneration (GBR) membranes are critical for reconstructing periodontal/bone defects, but existing membranes face limitations in osteogenic potential, antibacterial efficacy, degradation kinetics, mechanical stability, and immunomodulation within the complex oral microenvironment. This review aims to explore cellular interactions between alveolar bone regenerative cells and GBR/GTR membranes, membrane design strategies based on biological functions, and advancements in material engineering to overcome current clinical challenges. A comprehensive search strategy was implemented across PubMed, Scopus, Web of Science databases, as well as clinical trials registers. Data pertinent to membrane synthetic methodology, biological behavior, tissue regeneration outcomes were retrieved from the original studies. A qualitative assessment was performed. Overall, ideal GBR/GTR membranes must meet several functional requirements: (i) Clinical necessities include biocompatibility, selective permeability for nutrient exchange, and clinical operability. GTR aims to create and maintain a stable isolated space to protect blood clots, thereby enabling blood clots and the newly formed tissue to effectively block the migration of epithelial cells. GBR demands rigid space maintenance to resist mucosal compression in edentulous ridges, with greater emphasis on mechanical stability for large bone defects. Degradation kinetics must align with slower bone formation (3–6 months). (ii) Appropriate surface properties (roughness, morphology, stiffness, wettability, charge) and porosity/pore size are critical for cell behavior. (iii) Membrane‐based biological regulation can promote cell adhesion and migration, and balance osteoclastogenesis and osteogenesis. Optimization strategies include incorporating bioactive substances for bone regeneration, immunomodulatory agents for anti‐inflammatory responses, and antibacterial additives for clinical performance. GBR/GTR membranes require multifunctional integration of barrier functionality, tailored biodegradation, mechanical robustness, and proactive bioactivity (osteogenic, angiogenic, immunomodulatory, and antibacterial). Future designs must prioritize understanding cell‐material interactions to develop membranes that dynamically synchronize with the regenerative microenvironment. This review provides a foundation for developing next‐generation membranes that effectively address complex oral microenvironment challenges and significantly improve clinical outcomes in bone defect reconstruction. Optimized membranes will enhance space maintenance, reduce infection rates, mitigate premature degradation, and improve predictability in reconstructing periodontal and alveolar bone defects, ultimately advancing regenerative outcomes in implant dentistry and periodontal surgery.